The Effect of Fintech Use on Personal Financial Management With Trust as a Mediating Variable in Generation Z - Ida Bagus Gde Indra Wedhana Purba; IA Cynthia Saisaria Mandasari; Ade Ruly Sumiartini (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of fintech use on personal financial management among Generation Z, with trust as a mediating variable. Data were collected through a survey of Generation Z users who actively use fintech services and analyzed using statistical regression and mediation analysis methods. The results indicate that fintech use has a positive and significant influence on personal financial management among Generation Z. Furthermore, trust acts as a partial mediator that strengthens this relationship. These findings indicate that user trust in fintech is crucial for improving the effectiveness of personal financial management. The practical implications of this study include the need to develop secure, transparent, and user-friendly fintech features, as well as improving digital financial literacy among Generation Z. Theoretically, this study strengthens the framework of the Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology by emphasizing the role of trust in financial technology adoption. This study opens up opportunities for further research to explore the factors influencing the effectiveness of fintech in the financial management of the younger generation.